The IL-10 polarized cytokine pattern in innate and adaptive immunity cells contribute to the development of FVIII inhibitors - Silveira, Amanda Cardoso de Oliveira (2015)
Fundação Oswaldo Cruz. Centro de Pesquisas René Rachou. Laboratório de Biomarcadores de Diagnóstico e Monitoração. Belo Horizonte, MG, Brasil.